Local Flavor, Global Spirit: Traditional Rujak Serut Training for UMKM With Dharma Wanita Universitas Terbuka Medan - riady, yasir; Pakpahan, Sondang Purnamasari; Marini, Yushita; Evriza, Eka; Lubis, Dewi Shinta Wulandari; Gurung, Lina (CV Media Inti Teknologi, 2025)
Background of study: This community service initiative seeks to enhance the abilities and inventiveness of members of the Dharma Wanita Persatuan (DWP) Universitas Terbuka (UT) Medan in the culinary domain, particularly in the preparation of traditional rujak serut.Aims and scope of paper: The main objective for Participants is to get expertise on selecting high-quality ingredients, employing appealing presentation tactics, and implementing basic marketing strategies to enhance the product's economic value.Methods: The methodologies employed encompass counselling, direct demonstrating, individual practi, and interactive conversations.Result: The activity's outcomes demonstrated significant enthusiasm among participants and enhanced proficiency in processing and turning rujak serut into commercially viable dishes.Conclusion: This program can be the initial step in strengthening the creative economy leveraging local potential for members of DWP UT Medan and also implementation of Tri Dharma University.